Topological insulator metamaterial with giant circular photogalvanic effect - Sun, X. (2021)
One of the most notable manifestations of electronic properties of topological insulators is the dependence of the photocurrent direction on the helicity of circularly polarized optical excitation. The helicity-dependent photocurrents, underpinned by spin-momentum locking of surface Dirac electrons, are weak and easily overshadowed by bulk contributions. Here, we show that the chiral response can be enhanced by nanostructuring. The tight confinement of electromagnetic fields in the resonant nanostructure enhances the photoexcitation of spin-polarized surface states of topological insulator Bi1.5Sb0.5Te1.8Se1.2, leading to an 11-fold increase of the circular photogalvanic effect and a previously unobserved photocurrent dichroism (ρcirc = 0.87) at room temperature. The control of spin transport in topological materials by structural design is a previously unrecognized ability of metamaterials that bridges the gap between nanophotonics and spin electronics, providing opportunities for developing polarization-sensitive photodetectors.